2021
DOI: 10.3390/s21062246
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Freezing of Gait during Walking Using Inertial Measurement Unit and Plantar Pressure Distribution Data

Abstract: Freezing of gait (FOG) is a sudden and highly disruptive gait dysfunction that appears in mid to late-stage Parkinson’s disease (PD) and can lead to falling and injury. A system that predicts freezing before it occurs or detects freezing immediately after onset would generate an opportunity for FOG prevention or mitigation and thus enhance safe mobility and quality of life. This research used accelerometer, gyroscope, and plantar pressure sensors to extract 861 features from walking data collected from 11 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 46 publications
(61 reference statements)
0
40
0
2
Order By: Relevance
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…Data were labeled as Non-FOG, Pre-FOG, or FOG. Pre-FOG was defined as 2 s of data before each FOG, as in [ 54 , 55 ]. The labeled data were divided into 1 s windows with 0.2 s shift between windows (i.e., 80% overlap) ( Fig 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ten features were extracted from each window. The features were calculated from lower-limb IMU and plantar pressure data and were selected by Relief-F feature ranking from among over 850 total features, described in [ 54 ]. The features used were the dominant fast Fourier transform (FFT) frequency of foot centre of pressure (COP) velocity in medial/lateral (ML) directions for the right leg and anterior/posterior (AP) for the right and left legs, the dominant FFT frequency of thigh accelerometers in the AP direction for the right and left legs, mean energy of wavelet transform (WT) approximation coefficient of COP position in the AP direction for the right leg, number of COP AP reversals for the right and left legs, mean of WT approximation coefficient for COP position in AP for the right leg, and the min of the COP detail coefficient in the AP direction for the right leg.…”
Section: Methodsmentioning
confidence: 99%
“…Plantar pressure has been used in rehabilitation strategies [ 23 26 ], fall-risk prediction [ 27 ] and classification [ 28 ] in older adults, and classifying gait as PD or healthy control [ 29 ]. Only recently, plantar pressure data has been used together with accelerometer data for FOG detection [ 30 ], and in our recent research for early FOG detection and prediction (together with IMU data [ 31 , 32 ] and alone [ 32 , 33 ]). Plantar pressure data was useful in detecting FOG and the transition from normal walking into a freeze.…”
Section: Introductionmentioning
confidence: 99%